2018
DOI: 10.1016/j.bandc.2018.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Goals matter: Amplification of the motivational significance of the feedback when goal impact is increased

Abstract: Performance monitoring (PM) entails the continuous evaluation of actions and their outcomes. At the electrophysiological level, PM has been consistently related to two event-related brain potentials (ERPs): the Feedback-Related Negativity (FRN) and the P3. In a previous withinsubject crossover design study, we showed that feedback's goal impact (i.e., its importance to one's goal) modulated these ERP components, yet in opposing directions. Although high goal impact was associated with a larger P3, the precedin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 118 publications
(175 reference statements)
0
9
1
Order By: Relevance
“…Relevance was understood in this study as the degree to which a stimulus was informative about the satisfaction status of pursued goals (see also Moors, ). Moreover, in another recent EEG study, we found evidence that goal relevance understood as impact increased the P3b during PM (Severo et al, , ). Impact corresponded to the amount of goal satisfaction that was signaled by the feedback stimulus.…”
Section: Discussionmentioning
confidence: 56%
See 4 more Smart Citations
“…Relevance was understood in this study as the degree to which a stimulus was informative about the satisfaction status of pursued goals (see also Moors, ). Moreover, in another recent EEG study, we found evidence that goal relevance understood as impact increased the P3b during PM (Severo et al, , ). Impact corresponded to the amount of goal satisfaction that was signaled by the feedback stimulus.…”
Section: Discussionmentioning
confidence: 56%
“…for each type of feedback separately; and (h) low-pass digital filtering of the individual average data (30 Hz). 4 In accordance with previous ERP studies focused on feedback-based PM (Aarts & Pourtois, 2012;Bismark, Hajcak, Whitworth, & Allen, 2013;Ferdinand et al, 2012;Fischer & Ullsperger, 2013;Pfabigan et al, 2011;Severo et al, 2017Severo et al, , 2018von Borries et al, 2013;Walentowska et al, 2016;Walsh & Anderson, 2012) as well as the electrophysiological properties of the current data set (see Figure 3), the FRN was defined as the mean voltage within 250-300 ms after feedback onset over frontal and frontocentral electrodes along the midline (Fz and FCz pooled together). The P3b amplitude was measured as a mean voltage between 350 and 600 ms after feedback onset at centroparietal and parietal electrodes (CPz and Pz pooled together).…”
Section: Eeg Acquisition and Erp Analysesmentioning
confidence: 75%
See 3 more Smart Citations